YURIY KRYVDIN – THE UNKNOWN NAME OF THE UKRAINIAN GRAPHIC DESIGN OF THE 1920–30s - Будник, А. В. (Art and Design, 2021)
Purpose: organize and analyze the legacy of a little-known artist, make an attempt to collect biographical data, trace the relationship of creative principles with world trends in graphic design of that period. Methodology. Historical-comparative and art-scientific methods of analysis were used for the research. Results. During the 1920s and 1930s, Ukrainian magazine graphics underwent a final transformation from the aesthetics of modern and eclecticism to the style of constructivism, which called for the work of masters of a new type of graphic thinking, such as Yuriy Kryvdin. The investigation for the first time analyzed the activities of a little-known representative of Ukrainian constructivism – Yuriy Kryvdin, who worked in the field of magazine graphics and layout, collage, book design. The influences of world tendencies of graphic design on creativity of the master, typology of imitation are investigated. Samples of the artist's autographs were collected and the publishing spheres to which the artist made efforts were systematized. His literary activity and its connection with artistic creativity are briefly reviewed. Scientific novelty.As for Kryvdin, there was no art criticism in the professional literature. For the first time, the sources that influenced the creative style of the master are highlighted, as well as the spheres of his activity are systematized. Practical significance. With the development of Ukrainian culture in the paradigm of an independent state, the importance of opening the little-known pages of the formation of national design, which gave the foundation of modern art.